2019
DOI: 10.3390/m1100
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N-Heterocyclic Analogues of 28-O-Methyl Betulinate, and Their Antibacterial and Antifungal Properties

Abstract: The paper presents the results on the one-pot pyridine quaternization using betulinic 28-O-methyl ester (1) and Tempo+Br3− cation followed by reduction of the resulting salt (2) to 1,2,5,6-tetrahydropyridine derivative (3). The structures of new compounds are confirmed by means of 1D and 2D-NMR spectroscopy, as well as MALDI TOF/TOF spectrometry. The derivatives 2 and 3 are active against S. aureus at the minimum inhibitory concentration (MIC) of 4 μg/mL and 16 μg/mL, correspondingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Given the reported key pharmacophore role played by the triazole moiety, it was employed by Sidova et al in the synthesis of BA-4-substituted-1,2,3-triazole derivatives via Cu-catalyzed Huisgen 1,3-cycloaddition to the C30 allylic group using C3 acetylated BA-derivatives as starting compounds; when tested in vitro against a panel of eight cancer and two normal cell lines, compound BA 53, containing an acetylated C3 and a 4-(2-formylphenyl)-1,2,3-triazole in the allylic position, showed significant cytotoxicity as well as selectivity against several types of leukemia cells such as CCRF-CEM (IC 50 = 3.3 µM), K562 (IC 50 = 3.6 µM), and K562-TAX (IC 50 =3.9 µM) [ 91 ]. The insertion of two other N-containing heterocycles, pyridine (BA 54) and tetrahydropyridine (BA 55) into C30 in the molecule of 28-O-methyl-BA resulted in improved antibacterial effects against Staphyloccocus aureus compared with the parent compound, thus indicating that aromatic or liphatic N-containing heterocycles could be used for the synthesis of antimicrobial BA derivatives [ 92 ].…”
Section: Betulinic Acidmentioning
confidence: 99%
“…Given the reported key pharmacophore role played by the triazole moiety, it was employed by Sidova et al in the synthesis of BA-4-substituted-1,2,3-triazole derivatives via Cu-catalyzed Huisgen 1,3-cycloaddition to the C30 allylic group using C3 acetylated BA-derivatives as starting compounds; when tested in vitro against a panel of eight cancer and two normal cell lines, compound BA 53, containing an acetylated C3 and a 4-(2-formylphenyl)-1,2,3-triazole in the allylic position, showed significant cytotoxicity as well as selectivity against several types of leukemia cells such as CCRF-CEM (IC 50 = 3.3 µM), K562 (IC 50 = 3.6 µM), and K562-TAX (IC 50 =3.9 µM) [ 91 ]. The insertion of two other N-containing heterocycles, pyridine (BA 54) and tetrahydropyridine (BA 55) into C30 in the molecule of 28-O-methyl-BA resulted in improved antibacterial effects against Staphyloccocus aureus compared with the parent compound, thus indicating that aromatic or liphatic N-containing heterocycles could be used for the synthesis of antimicrobial BA derivatives [ 92 ].…”
Section: Betulinic Acidmentioning
confidence: 99%
“…[11][12][13][14][15] As a rule, the synthesis of quaternized betulin derivatives goes through several stages, [11][12][13][14] including the preliminary protection of functional groups, the preparation of bromo analogs (I) and their further reaction with amines or pyridines to give target products (II) (Scheme 1, route A). Previously, we have developed an efficient one-pot method for the synthesis of pyridinium semi-synthetic analogs of the lupane-type triterpenoids (Scheme 1, route B), [15][16][17][18][19] which involves the reaction of the starting substrates with organic tribromides (2,2,6,6-a Institute of Petrochemistry and Catalysis, Ufa Federal Research Center, Russian Academy of Sciences, 141 Prospekt Oktyabrya, Ufa 450075, Russian Federation b Institute of Cytology of Russian Academy of Sciences, 4 Tikhoretsky prospect, 194064, Saint Petersburg, Russian Federation. E-mail: luda_parfenova@ipc-ras.ru † Electronic supplementary information (ESI) available: Table S1: Growth inhibition (%) of compounds 1-9, 1a-9a, 1b-7b, 9b, 1c-9c, 1d, 3d, 4d, 1e, 3e, and 9e at concentration 32 mg mL À1 .…”
Section: Introductionmentioning
confidence: 99%
“…Using the developed strategy, 6 examples of lupane triterpene analogs 1a-c, 2a, 3a, 4a were synthesized (Scheme 1), which showed pronounced antimicrobial activity and membranotropic properties. [15][16][17][18][19] Moreover, quaternary salts of fusidanes and ecdysteroids were synthesized by this approach. 20,21 It has been shown that the reaction proceed via both radical allylic bromination and electrophilic addition, depending on the degree of substitution and the position of the double bond in the molecule.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations